Monitoring Insect Transposable Elements in Large Double-Stranded DNA Viruses Reveals Host-to-Virus and Virus-to-Virus Transposition. (30th June 2021) - Loiseau, Vincent; Peccoud, Jean; Bouzar, Clémence; Guillier, Sandra; Fan, Jiangbin; Gueli Alletti, Gianpiero; Meignin, Carine; Herniou, Elisabeth A; Federici, Brian A; Wennmann, Jörg T; Jehle, Johannes A; Cordaux, Richard; et al.
Abstract: The mechanisms by which transposable elements (TEs) can be horizontally transferred between animals are unknown, but viruses are possible candidate vectors. Here, we surveyed the presence of host-derived TEs in viral genomes in 35 deep sequencing data sets produced from 11 host–virus systems, encompassing nine arthropod host species (five lepidopterans, two dipterans, and two crustaceans) and six different double-stranded (ds) DNA viruses (four baculoviruses and two iridoviruses). We found evidence of viral-borne TEs in 14 data sets, with frequencies of viral genomes carrying a TE ranging from 0.01% to 26.33% for baculoviruses and from 0.45% to 7.36% for iridoviruses. The analysis of viral populations separated by a single replication cycle revealed that viral-borne TEs originating from an initial host species can be retrieved after viral replication in another host species, sometimes at higher frequencies. Furthermore, we detected a strong increase in the number of integrations in a viral population for a TE absent from the hosts' genomes, indicating that this TE has undergone intense transposition within the viral population. Finally, we provide evidence that many TEs found integrated in viral genomes (15/41) have been horizontally transferred in insects. Altogether, our results indicate that multiple large dsDNA viruses have the capacity to shuttle TEs in insects and they underline the potential of viruses to act as vectors of horizontal transfer of TEs. Furthermore, the finding that TEs can transpose between viral genomes of a viral species sets viruses as possible new niches in which TEs can persist and evolve.